2023
DOI: 10.1186/s12903-023-02904-4
|View full text |Cite|
|
Sign up to set email alerts
|

Critical review on quality of methodology and recommendations of clinical practice guidelines for peri-implantitis

Abstract: Background Peri-implantitis is of high prevalence with the popularity of dental implants nowadays. Guidelines or consensus have been developed in succession, and we are little-known about their quality. The objective of this study is to evaluate the methodological quality of these guidelines and analyze the consistency of the clinical recommendations. Methods We searched for guidelines or consensus on prevention, diagnosis, and/or treatment of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Two independent experts used the Appraisal of Guidelines for Research and Evaluation (AGREE) II [22,23]. This solution is well-known, proven and has been frequently used to date to evaluate medical devices and procedures [24][25][26][27][28], including exoskeletons [29]. The PubMed database shows 1231 publications with the keyword "AGREE II".…”
Section: Methodsmentioning
confidence: 99%
“…Two independent experts used the Appraisal of Guidelines for Research and Evaluation (AGREE) II [22,23]. This solution is well-known, proven and has been frequently used to date to evaluate medical devices and procedures [24][25][26][27][28], including exoskeletons [29]. The PubMed database shows 1231 publications with the keyword "AGREE II".…”
Section: Methodsmentioning
confidence: 99%
“…Micro-CT is a common method for analyzing alveolar bone loss. Vertical bone loss, which is assessed by measuring the linear distance between the implant neck and the lowest point of the alveolar bone, was used to evaluate alveolar bone destruction around implants (Yin et al, 2023). The results showed that the composite hydrogels with ultrasound stimulation group exhibited significantly less bone destruction than the peri-implantitis group (Figure 6C).…”
Section: In Vivo Inflammatory Regulation and Bone Repair Analysismentioning
confidence: 99%